Circus Tribute to the Tenth Muse Cirque du Soleil and the Performance „Iris” - Zyzik, Grzegorz (Not just the Clown and the Tiger. Sketches about Circus Arts, 2019)
The aim of the author is to describe the process of transcription of the history of the cinema into the language of the circus. The artists from Cirque du Soleil showed a performance Iris inspired by the legendary films such as Gone with the Wind and Titanic. Combining dance, acrobatics, video, filmed live sequences and animations, the performance takes the audience on a journey through the history of the cinema and a diverse range of film genres, introducing them to the world of filmmaking. Moving from illustration to animation, from the blackand- white picture to color, viewers can follow the construction and deconstruction of the film art as a discipline and a peculiar way of crossing the boundaries of what is possible. The author puts forward a hypothesis that the show Iris aims to evoke feelings that accompanied first cinema viewers. It refers to the nostalgia for the time when the cinema was like a circus. It is worth remembering that the first screenings were of the fair nature, similar to the classic circus. Today both the cinema and circus have the status of art.